Motivation for Mountain Women in Rural Development - Ismail, Ashari (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
This research is a research that describes the motivation of women's occupation in rural development. This basic research is set in the Pengkasalu community, West Kaili Suli Village, Luwu. It is understood that women's occupational motivation is a problematic part of every community that needs to be revealed, in order to focus on excellent and reliable motivation in every development role. In this research, the method or approach used is a descriptive method with a qualitative approach. A qualitative approach is an approach that seeks to reveal research problems, by understanding the subjective data of the target through interviews, observations, and documentation. While the descriptive method is a method by describing observed social phenomena. The results of this research show that women's work motivation is made possible by the need factor to meet basic needs, the fulfillment of the need to socialize, and also for self-actualization. This work motivation is a work motivation born from the awareness of village women about the urgency of participating in the development and fulfillment of family needs. With the motivation born from the role of women, it is possible to give birth to a role and empowerment in the Pengkasalu community, in domestic and public roles.